UNESCO plaque at Shiv Shanti Bhuvan - Ghosh, Ayan (Jio Institute, 2023)
UNESCO plaque at Shiv Shanti Bhuvan, recognizing the building as part of the Victorian Gothic and Art Deco Ensembles of Mumbai in 2018.